Gardon gauge heat flux sensor verification by new working facility. (February 2019) - Purpura, C.; Trifoni, E.; Petrella, O.; Marciano, L.; Musto, M.; Rotondo, G.
Highlight: Working standard for a functional verification of Gardon gauge is presented. Working standard achieves high value of thermal flux by using a radiative and convective as thermal sources. Good repeatability, reproducibility and adequate uncertainty value (less than 3%). Abstract: In the present paper, a novel working standard for metrological verification of Gardon gauge (Gg) is presented. The authors propose to couple the radiative and convective thermal sources in order to achieve high values of thermal flux. This is particularly important for those laboratories where high heat flux values have to be measured, such as on ground test facilities for the simulation of spacecraft re-entry. These test facilities, frequently, have the need to verify their Gardon gauges through working standards, before each running test. Unfortunately, the common Black Body temperature does not allow to reach the desired heat flux values to verify these kinds of probe. The proposed working standard, instead, allows to achieve heat flux values higher than those reachable with only the radiative flux emitted by the Black Body, of at least one order of magnitude. The experimental tests have shown high repeatability of the measurements; this proves the feasibility of this kind of verification technique. In addition, the authors have assembled a further working standard to evaluate the reproducibility of the proposed technique. In fact, the low values of compatibility index (less than 1) indicate that the proposed technique has also a satisfactory reproducibility.